2014
DOI: 10.2169/internalmedicine.53.1639
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Therapy was Effective in Controlling Refractory Coronary Vasospasms Complicated by Hypereosinophilia

Abstract: A 48-year-old man suffered from uncontrollable coronary vasospasms, even when taking the maximum dose of vasodilators. The patient had a history of hypereosinophilia, and as the eosinophilia worsened, more frequent and intense coronary spastic angina (CSA) attacks occurred. He was treated with 20 mg/day of oral prednisolone, and the chest symptoms of CSA completely resolved thereafter. We encountered a refractory CSA patient with an allergic predisposition for which the oral administration of corticosteroids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…For such refractory CSA cases, steroids are an available treatment option. Previous reports have shown that the symptoms exhibited by six patients with CSA were relieved after corticosteroid administration (Table 3) (20)(21)(22). All of the patients had some allergic comorbidities, and five of them had a history of asthma.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For such refractory CSA cases, steroids are an available treatment option. Previous reports have shown that the symptoms exhibited by six patients with CSA were relieved after corticosteroid administration (Table 3) (20)(21)(22). All of the patients had some allergic comorbidities, and five of them had a history of asthma.…”
Section: Discussionmentioning
confidence: 82%
“…Two of them had worsening symptoms of asthma, and another two demonstrated eosinophilia and elevated immunoglobulin E (IgE) levels concurrent with their CSA symptoms. These reports suggest that the CSA spasm may be induced by arterial hyperactivity or allergic angiitis caused by local inflammation, and corticosteroids can suppress the spasm by alleviating inflammation in the vessel wall ( 20 , 21 ). In the cases detailed in Table 3 , five out of six patients were treated with prednisolone, although in our patient's case, a small dose of dexamethasone was administered at bedtime in addition to regular hydrocortisone replacement.…”
Section: Discussionmentioning
confidence: 99%
“…EGPA is a rare autoimmune condition that typically presents with adult-onset asthma, migratory pulmonary infiltrates, peripheral eosinophilia, paranasal sinus abnormalities, and 40% of cases may have antineutrophil cytoplasmic antibodies-associated focal segmental glomerulonephritis. As discussed above, cardiac manifestations of EGPA rarely include coronary artery vasospasm although some case reports have been published [4,5]. None of the previous cases presented with cardiogenic shock requiring multiple modalities for blood pressure support.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids was effective in treating patients with refractory VSA, who had allergic disease (e.g. bronchial asthma, chronic thyroiditis, and Raynaud phenomenon) 46,57) , hypereosinophilia [58][59][60][61] , and adventitial focal inflammatory cells infiltration 62) .…”
Section: Corticosteroidmentioning
confidence: 99%